Histopathological profile and radiological features of lung cancer with and without a history of pulmonary tuberculosis at dr. Zainoel Abidin Hospital, Banda Aceh - Mardhatillah; Kurniawan, Ferry Dwi; Maulina, Novi; Arliny, Yunita; Sakdiah; Andayani, Novita (Journal of International Surgery and Clinical Medicine, 2024)
Introduction: Lung cancer is one of the types of malignancies that is the leading cause of cancer deaths worldwide. In Indonesia, the incidence of lung cancer is quite high, with pulmonary TB as a risk factor that can increase the risk of lung cancer in the future. This study aims to describe the histopathological profile and radiological picture of lung cancer patients in patients with and without a history of pulmonary TB at dr. Zainoel Abidin Hospital Banda Aceh. Methods: This study uses retrospective methods and univariate analysis. The subjects of this study are lung cancer patients at dr. Zainoel Abidin Hospital from January 2022 to December 2023. Result: The results of this study showed that of the 184 patients, 6.5% of them had lung cancer with a history of pulmonary TB, while the other 93.5% had lung cancer without a history of pulmonary TB. Of the two groups of lung cancer, the majority of patients were aged 51-60 years (32.6%), male (83.7%), still working (81%), from Aceh (99.5%), and Muslim (99.5%). Most lung cancer patients were diagnosed at stage IV (86.4%), with Squamous Cell Carcinoma being the most common type of histopathology (57.1%). In lung cancer patients with a history of pulmonary TB, post-TB lesions are often found, such as fibrosis (83.3%), calcification (50%), cavitation (33.3%), pleural thickening (16.7%), and atelectasis (8.3%). Conclusion: Efforts to prevent lung cancer, especially in patients with a history of pulmonary TB, need to be continued so that the risk of developing lung cancer can be reduced.